2022
DOI: 10.3390/molecules27238309
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Influence of ZnO, CrZnO, RuZnO, and BaZnO Nanomaterials on Bacterial Growth

Abstract: In this work, ZnO, CrZnO, RuZnO, and BaZnO nanomaterials were synthesized and characterized in order to study their antibacterial activity. The agar well diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays were used to determine the antibacterial activity of the fabricated nanomaterials against Staphylococcus aureus ATCC 29213, Escherichia coli ATCC35218, Klebsiella pneumoniae ATCC 7000603, and Pseudomonas aeruginosa ATCC 278533. The well-diffusion test reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…From the figure, it can be recorded that various sharp peaks were observed at two theta = 31.6, 34.4, 36.2, 47.4, 56.5, 62.7, 66.3, 69.0, and 69.3 are assigned to (100), ( 002), ( 101), ( 102), ( 110), ( 103), ( 200), (112), and (201) planes, respectively, of the wurtzite hexagonal ZnO crystalline nature. In compliance with JCPDS card number 88-0322, new peaks matching to 2 theta = 28.0, 35.0, and 54.4 were identified, characterizing the RuO2 rutile phase's (110), (101), and (211) planes [31]. On the basis of XRD patterns, Scherer's approach was utilized to compute the average crystallite size of nanostructurecompound [26].The average crystallite size of the RuO2@ZnO nanostructure compound were found to be to be 39.4 nm.…”
Section: Xrd Profile Of Ruo 2 @Znomentioning
confidence: 61%
“…From the figure, it can be recorded that various sharp peaks were observed at two theta = 31.6, 34.4, 36.2, 47.4, 56.5, 62.7, 66.3, 69.0, and 69.3 are assigned to (100), ( 002), ( 101), ( 102), ( 110), ( 103), ( 200), (112), and (201) planes, respectively, of the wurtzite hexagonal ZnO crystalline nature. In compliance with JCPDS card number 88-0322, new peaks matching to 2 theta = 28.0, 35.0, and 54.4 were identified, characterizing the RuO2 rutile phase's (110), (101), and (211) planes [31]. On the basis of XRD patterns, Scherer's approach was utilized to compute the average crystallite size of nanostructurecompound [26].The average crystallite size of the RuO2@ZnO nanostructure compound were found to be to be 39.4 nm.…”
Section: Xrd Profile Of Ruo 2 @Znomentioning
confidence: 61%
“…We evaluated the antibacterial activity, antibacterial mechanism and biosafety of MIL-101(Fe)@ZnO(1:0.5). FTIR, UV-vis, ICP-OES, XRD, SEM, EDS and BET showed that ZnO was successfully encapsulated in MIL-101(Fe) and MIL-101(Fe)@ZnO(1:0.5) had distinct characteristic diffraction peaks and high crystallinity, without structural collapse [18,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, zinc or zinc oxide has the advantages of small size effect of raw materials, surface effect, cheap price, abundant resources and non-toxic effect on the environment, etc. [18]. Currently, antimicrobial materials containing zinc or zinc oxide have been gradually applied in many fields such as food packaging, textiles, biomedicine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles serve as transport vehicles for antibacterial drugs, effectively fusing with the bacterial membrane. This enables the targeted delivery of the antibacterial agent directly to the bacterial cell, resulting in the eradication of the bacteria [173]. The green synthesis of silver nanoparticles (AgNPs) incorporated with aqueous extracts of Thymus vulgaris, Mentha piperita, and Zingiber officinale exhibited significant antibacterial activity against three multidrug-resistant clinical isolates, namely, Escherichia coli, Acinetobacter baumannii, and Staphylococcus aureus [174].…”
Section: The Synergistic Activity Of Plant Molecules With Nanomaterialsmentioning
confidence: 99%